The Influence Factors on Stock Returns of Real Estate and Property Companies Listed in Bei in 2010 - 2014 - Mayang, Putri (Jurnal Indonesia Sosial Sains, 2024)
This research seeks to examine and offer insights into the factors that impact stock returns of real estate and property companies listed on the Indonesia Stock Exchange. The examined factors include DER, EPS, NPM, PBV, inflation, exchange rate, SBI, and GDP. The research focuses on real estate and property companies listed on the Indonesia Stock Exchange during the 2010-2014 period, involving a total of 38 companies. The study analyzes the impact of these variables DER, EPS, NPM, PBV, inflation, exchange rate, SBI, and GDP on the stock returns of these companies. Data were collected from sources such as Bank Indonesia, the Central Bureau of Statistics, and the Indonesia Stock Exchange. The findings reveal that DER, EPS, NPM, and PBV significantly influence stock returns, whereas inflation, exchange rate, SBI, and GDP do not have a significant impact on the stock returns of real estate and property companies.